Sports-specific adaptation of left ventricular muscle mass in athlete's heart. I. An echocardiographic study with combined isometric and dynamic exercise trained athletes (male and female rowers) - Urhausen, A.; Monz, T.; Kindermann, W. (International Journal of Sports Medicine, 1996)
The differentiation of the physiological left ventricular (LV) hypertrophy of the athlete's heart in opposition to a pathological finding may be problematic especially in both strength and endurance trained athletes with simultaneously large body dimensions: 64 male and 71 female rowers of regional up to national level were examined by (Doppler) echocardiography. In addition, the rowers were compared by matched-pair procedures both with 32 male and 30 female non-endurance trained (pairwise similar body surface area) and with 28 male endurance athletes (pairwise similar absolute heart volume). The so-called critical heart weight of 500 g was exceeded by 63% of the male and 11% of the female rowers. 9% of the male rowers showed even an LV muscle mass above the limit of 3.5 g.kg-1 body mass. The individual maximal body surface area-related values were 170 g.m-2 (men) and 133 g.m-2 (women). The LV enddiastolic internal diameter was measured to be above the upper clinical limit of 55 mm in 69% or 23% of the male and female rowers, although a maximal LV wall thickness of 14 or 13 mm, respectively, was never exceeded. The systolic LV function as well as ECG and blood pressure did not reveal any pathological findings, the diastolic LV function was measured within the (supra) normal range. The LV wall thicknesses, internal diameter and hypertrophic index (relation between wall thickness and internal diameter) were significantly higher in rowers than in non-endurance trained subjects, but similar if compared to the endurance athletes. The clinical limits, however, keep their validity until a body mass of about 70 kg. In conclusion, some upper absolute clinical limits, especially those referring to volume measurements, so far considered critical (LV internal diameter, heart weight and LV mass), may be clearly exceeded by healthy strength endurance trained athletes presenting high body dimensions. The LV wall thickness, however, rather exceptionally exceeded the clinical limits. If referring to body dimensions, the cardiac dimensions in rowers are still lower in comparison to highly-trained "pure" endurance athletes. A specific influence of the isometric exercise component on the LV hypertrophy cannot be observed.